2020
DOI: 10.15252/embr.202050944
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in the frequency and position of mitosis in the mouse embryo epiblast at gastrulation

Abstract: At gastrulation, a subpopulation of epiblast cells constitutes a transient posteriorly located structure called the primitive streak, where cells that undergo epithelial–mesenchymal transition make up the mesoderm and endoderm lineages. Mouse embryo epiblast cells were labelled ubiquitously or in a mosaic fashion. Cell shape, packing, organization and division were recorded through live imaging during primitive streak formation. Posterior epiblast displays a higher frequency of rosettes, some of which associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Intravital imaging of inoculated human colon cancer cells showed that cells in S/G2/M phases were more motile and invasive than G1 cells [40]. In the mouse embryo, while the EMTtriggering transcription factor Snail blocks the cell cycle in the neural epithelium or allantois at E8.5 [41], we and others found an increased mitotic index in the Snail-enriched primitive streak at E7 [42,43].…”
Section: Epithelial-mesenchymal Transitionsupporting
confidence: 46%
See 4 more Smart Citations
“…Intravital imaging of inoculated human colon cancer cells showed that cells in S/G2/M phases were more motile and invasive than G1 cells [40]. In the mouse embryo, while the EMTtriggering transcription factor Snail blocks the cell cycle in the neural epithelium or allantois at E8.5 [41], we and others found an increased mitotic index in the Snail-enriched primitive streak at E7 [42,43].…”
Section: Epithelial-mesenchymal Transitionsupporting
confidence: 46%
“…We found that the large majority of non-apical mitosis in the mouse embryo epithelial epiblast at the primitive streak gave rise to one or two mesenchymal mesoderm daughter cells, while apical mitosis resulted in epithelial epiblast daughter cells [42]. Non-apical mitosis in the primitive streak might thus help the exit of nascent mesoderm cells from the epiblast through loss of cellcell adhesion, modification of the spatial pattern of forces favoring basement membrane breakage, and/or increased epithelium fluidity (Figure 4).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations